The Semantic Fields of Selected Ethical Terms in the Written and Web Subcorpus of the Slovak National Corpus - Debnar, Marek (Communications - Scientific letters of the University of Zilina, 2017)
The paper investigates the issue of semantic field of selected ethical terminology (e.g. morality, conscience, moral action, etc.) in the Slovak National Corpus (SNC). The examination covers two different subcorpuses (written and web) containing a collection of about thousand text units. The basic framework of written subcorpus consists of scientific articles from the field of humanities, religion and art. The web subcorpus was generated from website www.salon.eu.sk offering essays and feuilletons published by the European and world press, with special focus on Central European countries. Firstly, the paper describes the way of designing and building these subcorpuses based on critical interpretation of text metadata, and, secondly, it focuses on the rate of occurrence for the subject areas − Domains and Subdomains − that refer to ethical terminology included in the SNC. The paper then outlines the ways of interpreting the statistical results of the quantitative occurrence of the selected word forms, and it also defines the ways of using the subcorpus not only for linguistic and literary purposes, but also in interdisciplinary research areas.